FRI0008 Evidence for increased activity of interleukin-6 (IL-6) in seropositive rheumatoid arthritis (RA+), and differential tumour necrosis factor (TNF) receptor expression between ra+ and seronegative ra. (23rd January 2014) - Skwarek, M.; Heschel, B.; Fantana, J.; Aringer, M.
Abstract : Background: Despite common pathogenetic events in the effector phase, increasing evidence suggests that RA+ is different from RF and anti-CCP-negative RA-. In particular, genetic evidence and somewhat differential responses to therapy distinguish these subgroups. The IL-6 receptor, consisting of the IL-6 receptor α-chain (CD126) and of glycoprotein 130 (CD130), which is also part of other receptors, can be differentially regulated in inflammatory conditions, as can the homotrimeric TNF receptorsI (CD120a) and II (CD120b). Objectives: To profile RA+ and RA- patients with regard to IL-6 and TNF receptors Methods: Peripheral blood mononuclear cells (PBMC) of RA+, RA- patients, and healthy individuals (HC) were compared. Most (91%) of the RA+ patients were also positive for anti-CCP antibodies. PBMC were immediately prepared from peripheral venous blood. Serum levels of IL-6 and soluble IL-6R (sIL-6R) were measured by ELISA. For determining the percentages of CD126, CD130, CD120a, and CD120b, positive cells, PBMC were stained with phycoerythrin (PE)-labelled specific or control antibodies. Cells were analyzed on a Becton Dickinson FACSCalibur fluorocytometer, gating for lymphocytes. Results: Disease activity (median (range) CDAI 15.5 (0.3-54.5) and 13.5 (4.4-33.4)) and disease duration (median 6 (0.04-66) vs. 3 (0.04-10) years) were not significantly different between RA+ and RA- patients, respectively. However, lymphocytes of RA+ and RA- patients differed in their lymphocyte expression of the IL-6 receptor and of CD120b+. The percentage of CD126+ lymphocytes in RA+ (48±13 (mean±SD) %) was decreased in comparison with RA- (61±12%, p=0.006) and HC (60±9%, p<0.0001) lymphocytes. Although to a lesser degree, the percentage of CD130+ lymphocytes in RA+ (51±10%) likewise tended to be decreased when compared to RA- (59±14%, p=0.12) and was decreased as compared to HC (59±11%, p=0.002). In contrast, CD120b+ lymphocytes (68±12%) were increased in RA+ patients as compared to RA- (59±11%, p=0.04) and HC (57±11, p=0.0002). In neither case, were any differences between RA- and HC significant. The percentages of CD120a+ lymphocytes were low in all groups. Nevertheless, the percentage of CD120a+ lymphocytes of RA- patients (median 1.6 (0.5-3.4) %) was increased as compared to HC (median 1.2 (0.4-3.1) % p=0.007) and tended to be increasedas compared to those of RA+ patients (median 1.1 (0.3-3%, p=0.053), which in turn were not significantly different from HC (p=0.9). Levels of IL-6 were higher in RA+ (median 8.8 (2-265.7) pg/ml) than in RA- (4.03 (1.2-17.46) pg/ml, p=0.03) sera. Similarly, sIL-6R was higher in RA+ (56.8±18.6 ng/ml) than RA- sera (40±12.8 ng/ml, p=0.02). Conclusions: Our findings show that sIL-6R was increased and membrane CD126 decreased, suggesting increased IL-6 and more shedding of IL-6 receptors in RA+ patients, but not RA- patients. Interestingly, while RA+ lymphocytes more commonly expressed membrane CD120b, CD120a was increased in the case of RA- lymphocytes. These differences between RA+ and RA- patients may have implications for the role of therapies targeting TNF and IL-6 (receptors), respectively. Disclosure of Interest: None Declared